Intelligent Identification of Cerebrospinal Fluid for the Diagnosis of Parkinson’s Disease - Chen, Huiting; Guo, Siyun; Zhuang, Zehong; Ouyang, Sixue; Lin, Peiru; Zheng, Zhiyuan; You, Yuanyuan; Zhou, Xiang; Li, Yuan; Lu, Jiajia; Liu, Ningxuan; Tao, Jia; et al. (Analytical chemistry (Washington), 2024)
Cerebrospinal fluid (CSF) biomarkers are more sensitive than the Movement Disorder Society (MDS) criteria for detecting prodromal Parkinson’s disease (PD). Early detection of PD provides the best chance for successful implementation of disease-modifying treatments, making it crucial to effectively identify CSF extracted from PD patients or normal individuals. In this study, an intelligent sensor array was built by using three metal–organic frameworks (MOFs) that exhibited varying catalytic kinetics after reacting with potential protein markers. Machine learning algorithms were used to process fingerprint response patterns, allowing for qualitative and quantitative assessment of the proteins. The results were robust and capable of discriminating between PD and non-PD patients via CSF detection. The k-nearest neighbor regression algorithm was used to predict MDS scores with a minimum mean square error of 38.88. The intelligent MOF sensor array is expected to promote the detection of CSF biomarkers due to its ability to identify multiple targets and could be used in conjunction with MDS criteria and other techniques to diagnose PD more sensitively and selectively.